Prevalence of myopia among teenager students of Orenburg city schools - A. E. Aprelev; S. V. Cherkasov; P. E. Serebryakova; A. A. Aprelev; P. S. Cherkasova (Российский офтальмологический журнал)
Purpose: to study the prevalence and manifestation features of myopia in students of educational schools in the city of Orenburg.Material and methods. 710 schoolchildren of Orenburg schools, aged 11 to 18, were examined.Results. Myopia was found to be the most common pathology of the eye, diagnosed in 33.5 % of schoolchildren. The most frequent was low myopia claiming 65.4 % of myopic cases, followed by moderate myopia (28.5 %) and high myopia (6.1 %). The highest occurrence of myopia was revealed in 11th and 8th grade students (respectively, 55.8 and 40,0 cases per 100 examined subjects). It was found out that the share of more severe myopia stages (moderate and high) in increasing in older age groups 5th-grade to 11th-grade students. We also showed that myopia prevalence is connected with head and spine injuries in the case history.Conclusion. Educational facilities need to introduce an effective system of myopia prevention and means of progression reduction.